Numerical Simulation Analysis of Seismic Fragility of Vertical Floating-roof Storage Tanks. Issue 1 (May 2021) - Wang, Mengzhu; Sun, Zongguang; Sun, Jiangang; Cui, Lifu
Abstract: To study seismic response of tank, 10 × 10 4 m 3 vertical floating-roof tank model is established. The probability relationship between the intensity measure and engineering demand parameters is established based on extensive nonlinear dynamic time-history analysis. Four failure modes of tank were determined, and seismic fragility curve of under each failure mode was obtained. The results show that under frequent earthquake, the exceeding probability of circumferential tensile damage, and instability of tank wall in intact state were 40% and uplift of the bottom sheet was 75%. Under design-based earthquake and rare earthquake, circumferential tensile damage was in intact state, and the exceeding probability of instability were 66.9% in medium damage and 52.9% in severe damage. The exceeding probability of bottom uplift in severe damage is 90%. The method takes the randomness of ground motion into account, which can provide an effective idea for the evaluation of the seismic safety of tank structure.